STUDENTS’ REACTION AND PREFERENCES TO TEACHERS’ FEEDBACK ON WEEKLY JOURNAL ACTIVITY AT ENGLISH EDUCATION DEPARTMENT OF UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Prastya, Rio Laksamana (Journal of Foreign Language Teaching and Learning, 2018)
The objective of this research was to reveal students? reaction and preferences to teachers? feedback on weekly journal activity. This study was qualitative research that the data were compiled from six students batch of 2015 at English Education Department of Universitas Muhammadiyah Yogyakarta through in-depth interviews. The results showed that, with regard to the reactions of the students were satisfied with teachers? feedback, showed enjoyment in learning, felt curious in learning, and got demotivated in learning.The result also showed that the students preferred written feedback to oral feedback as they were easier to identify their errors, and oral feedback became second choice to comment their work. The students also believed that language and behavior of the teachers became the strongest effect creating the reaction of the students. On giving feedback, the teacher sometimes delivered it by using casual language that made the students easy to understand the feedback. Apparently, the language used by the teacher on delivering the feedback sometimes the teacher used funny words, so it could make the students enthusiasm to learn.